2006
DOI: 10.1099/jmm.0.46310-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 19 major virulence genes in Legionella pneumophila serogroup 1 isolates from patients and water in Queensland, Australia

Abstract: The distribution of 19 major virulence genes and the presence of plasmids were surveyed in 141 Legionella pneumophila serogroup (SG) 1 isolates from patients and water in Queensland, Australia. The results showed that 16 of the virulence genes examined were present in all isolates, suggesting that they are life-essential genes for isolates in the environment and host cells. The 65 kb pathogenicity island identified originally in strain Philadelphia-1 T was detected more frequently in isolates from water (44?2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
(47 reference statements)
3
20
0
Order By: Relevance
“…Specific genetic loci lvh and rtxA were chosen because they were suggested as appropriate indicators of L. pneumophila virulence after 19 major virulence genes were studied (42). A genetic element of the lvh locus in the genome of strain Philadelphia 1 (derived from the strain of the first outbreak in Philadelphia, PA) was detected in the genome of an Lp6 strain that has been sequenced in Canada (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific genetic loci lvh and rtxA were chosen because they were suggested as appropriate indicators of L. pneumophila virulence after 19 major virulence genes were studied (42). A genetic element of the lvh locus in the genome of strain Philadelphia 1 (derived from the strain of the first outbreak in Philadelphia, PA) was detected in the genome of an Lp6 strain that has been sequenced in Canada (43).…”
Section: Discussionmentioning
confidence: 99%
“…rtxA encodes the dot/icm-regulated pore-forming toxin and plays a significant role in the entry of the bacteria into the host cell (17). Rtx toxin consists of two regions; the N-terminal region is responsible for adhesion, and the C-terminal region participates in adhesion and pore formation (42).…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study showed that the distribution of lepA, lidA, ralF, rtxA and lvhB virulence genes were 11.1% (2/18), 50% (9/18), 27.7% (5/18), 5.5% (1/18) and 16.6% (3/18) with the higher prevalence in male patients with the exception of ralF and lvhB gene. Huang et al (2006) [28] showed that the incidence of lvh and rtxA genes in patients with clinical manifestations of L. pneumophila were 57.6% and 64.4%, respectively. RtxA positive strains of L. pneumophila have been shown to have a high capability to enter to monocytes and epithelial cells, and increased cytotoxicity and intracellular duplication [7].…”
Section: Resultsmentioning
confidence: 99%
“…The 65 kb pathogenicity island identified originally in strain Philadelphia-1T was detected more frequently in isolates from water (44.2%) than in those from patients (2.7%), indicating that the 65 kb DNA fragment may aid the survival of L. pneumophila in the sampled environment. However, the low frequency of the 65 kb fragment in isolates from patients suggests that the pathogenicity island may not be necessary for L. pneumophila to cause disease [35]. Zhu et al [36] reported the detection of 12 loci of putative pathogenicity island (iraA, iraB, mimP, irvA, ivhB, ivhD, cpxR, cpxA, dotA, rpoB, icmC, and icmD) for The virulence of Legionella may be increased by replication in amoeba.…”
Section: A 65 Kilobase Pathogenicity Island Locusmentioning
confidence: 99%